An early-type galaxy with an inner star-forming disc. Issue 2 (27th July 2018) - Li, Song-lin; Shi, Yong; Chen, Yan-Mei; Tabor, Martha; Bizyaev, Dmitry; Chen, Jian-hang; Yu, Xiao-ling; Bing, Long-ji
ABSTRACT: Early-type galaxies (ETGs) are composed of two distinct populations: high-mass and low-mass, which are likely to be built via gas-poor merging and gas-rich merging/accretion, respectively. However, it is difficult to directly associate low-mass ETGs with gas-rich processes because currently they are gas poor with no signs of ongoing star formation. We report a discovery of an ETG (SDSS J142055.01+400715.7) with M * = 10 10 M⊙ that offers direct evidence for gas-rich merging as the origin of low-mass ETGs. The integrated properties of the galaxy are consistent with a typical low-mass ETG, but the outer and inner regions show distinct dispersion- and rotation-dominated kinematics, respectively. There are some tidal features surrounding the galaxy. These two facts suggest very recent galaxy merging. Furthermore, the inner disc harbors ongoing star formation, indicating the merging to be gas rich. This type of galaxy is rare, but it may be a demonstration of the role the transient phase of gas-rich merging plays in making a low-mass ETG.